Curriculum-Based Assessment of Oral Language and Listening Comprehension: A Tool for Intervention and Progress Monitoring in the Common Core State Standards - Robinson, Wendy (Seminars in Speech and Language, 2012)
The Common Core State Standards and a Response to Intervention framework are movements sweeping the nation. Speech-language pathologists are uniquely positioned to play a pivotal role in supporting successful implementation of these movements. This article explores the assessment tools speech-language pathologists SLPs will need to identify and progress monitor critical language/literacy skills such as listening comprehension and oral narratives skills. Foundational research demonstrates that communication units, total words spoken, and major story components are measures that will discriminate between students with adequate language skills and language disorders and are curriculum-based, sensitive to change, and useful to determine the effectiveness of language/literacy interventions. Speech-language pathologist can broaden the impact of their knowledge and skills to improve outcomes for all students.
Keywords: common core state standards; listening comprehension; oral narratives; progress monitoring; language/literacy skills